"You shouldn't" Three observations on the necessity of moral education - Jan Hábl (Czech Pedagogical Society, 2014)
The goal of this study is to deal with three reasons explaining the importance and necessity of moral education - not just in schools but in general. The research question is: Why do we need moral education? Each subchapter of this study will provide answers or grounds from which the necessity of moral education will be deduced, and which I intend to expose in this study. They apply to three particular areas: 1) the nature of the human being as a moral being, 2) the nature of moral reality itself, and 3) the specific nature of the postmodern situation in which we recognize the need for moral formation. The analysis of the three phenomena provides an argument for traditional moral realism which not only grounds any moral education but also makes it possible. Moral education proves to be not merely necessary but also philosophically legitimate.